The Broken Plural and the Indonesian Translation in Salahuddin Al Ayyubi Cartoon Series - Hafsah, Lutfiah; Kholisin, Kholisin; Lafta, Awad Kadhim (Universitas Islam Negeri Raden Intan Lampung, 2024)
This article presented the determine of characteristics of the jama' taksir patterns that appear most in the cartoon series and determine how to translate the jama' taksir into Indonesian. This is a qualitative descriptive research. The research data came from sentences or conversations containing the jama' taksir in the Salahuddin Al-Ayyubi cartoon series which consists of 15 episodes. Based on the research, the Jama' qillah pattern أفعال is the most frequently occurring pattern. In the jama' katsrah, the patterns فعول, فعال, فعلاء and أفعلاء often appear. Meanwhile, Shighat muntaha al-jumu' patterns that often appear are مفاعل, فعاليل, and فواعل. The emergence of the jama' taksir that applies to the isim tsulatsi; أفعال, فعول and فعال, are counted more than that, regardless of the genre of the text. It was influenced by the genre of the text. Jama' taksir in this cartoon series was translated into Indonesian with 5 forms, namely: 1) Reduplication, 2) Numeral followed by a singular word, 3) Indefinite numeral followed by a singular word, 4) Singular word preceded by a plural marker and 5) Singular word. The translation of the jama' taksir must follow the grammatical rules of the Indonesian language, for example, the jama' taksir cannot always be translated with repetition. If there is already a plural marker, the jama' taksir is simply translated with the singular form. The results of this study can be used by translators as knowledge when translating jama' taksir and can also be used as reference material in further studies.